QMIX : ação sobre endotoxina bacteriana e efeito da combinação com hipoclorito de sódio sobre as paredes do canal radicular - Gründling, Grasiela Sabrina Longhi (2014)
This thesis had the purpose to evaluate the action of a new irrigant, QMix, on bacterial endotoxins as well as the effect of its combination with sodium hypochlorite on the root canal walls. Having the main purpose to evaluate its action on bacterial endotoxins, 50 extracted human teeth were contaminated in vitro with endotoxins and irrigated with QMix, EDTA, chlorhexidine (CHX) and sodium hypochlorite (NaOCl). It was used a Limulus Amebocyte Lysate (LAL) assay to quantify the remaining endotoxins after the irrigation. The results of this first study showed that QMix reduced the endotoxins level when compared to the other irrigant solutions that were tested. The second study from this thesis had the purpose to observe in scanning electron microscopy (SEM) the formation of precipitate on the root canal walls due to the concomitant use of NaOCl and QMix. The results from this study showed that despite the presence of CHX in the composition of QMix, its use after the chemical mechanical preparation of the canal with NaOCl did not result in the formation of a precipitate on the root canal walls. On the contrary, the images in SEM showed clean walls with exposed dentinal tubules. Once it is a new product there are still few studies about QMix. Although, according to the results presented on this study, it can be concluded that QMix is effective on the elimination of bacterial endotoxins from the root canal, not showing any precipitate formation when used concomitantly with NaOCl.